PERBEDAAN PENYULUHAN METODE DONGENG DAN PERMAINAN MONOPOLI TERHADAP PENGETAHUAN MENYIKAT GIGI PADA KELOMPOK USIA 9-10 TAHUN DI SDN 1 PALAM BANJARBARU - Rini Jusy Fitriana; Siti salamah (Politeknik Kementerian Kesehatan Banjarmasin, 2019)
Dental and oral health problems are quite high (> 35%), namely South Kalimantan. One of the health professionals who can improve dental and oral health knowledge is usually done by counseling. The method used is a didactic method only active educators and the socratic method of educators and students being active and creative. This study aims to determine the differences in counseling of fairy tales methods and monopoly games on knowledge of tooth brushing in the 9-10 year age group in SDN 1 Palam Banjarbaru. This type of research is analytical. This research design is quasi-experimental. This study was a pretest-posttest design. The number of samples is 71 respondents using total sampling or saturated sampling techniques. The results of this study indicate that the use of fairy tale methods and monopoly game methods can both increase the knowledge of brushing teeth, but the average extension knowledge using the monopoly game method is higher than the fairy tale method, it can be seen from the magnitude of the average knowledge of brushing before counseling ( 10.25), after counseling (12.33) and the average difference (2.08) using the monopoly game method. Compared to the average value of tooth brushing knowledge before counseling (10.26), after counseling (11.49) and the average difference (1.23) using a fairy tale method.The conclusion is that there are differences in the extension of fairy tale methods and the monopoly game method of knowledge of brushing teeth in the 9-10 year age group at SDN 1 Palam Banjarbaru.